TMS320F2812 Digital Signal Processor (DSP) implementation of DPWM - Mohd Faridun Naim, Tajuddin; Ghazali, N. H.; Mohd Fayzul, Mohammed; Baharuddin, Ismail, Dr.; Mat Isa, Zainuddin; Siong, T. C.; Ghazali, N. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/